2014
DOI: 10.1007/978-3-319-12114-7_1
|View full text |Cite
|
Sign up to set email alerts
|

Prolactin (PRL) in Adipose Tissue: Regulation and Functions

Abstract: New information concerning the effects of prolactin (PRL) on metabolic processes warrants reevaluation of its overall metabolic actions. PRL affects metabolic homeostasis by regulating key enzymes and transporters associated with glucose and lipid metabolism in several target organs. In the lactating mammary gland, PRL increases the production of milk proteins, lactose, and lipids. In adipose tissue, PRL generally suppresses lipid storage and adipokine release and affect adipogenesis. A specific case is made f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(33 citation statements)
references
References 127 publications
0
29
0
1
Order By: Relevance
“…Physiological mechanisms related to lactation that could increase LST need further study, but hormones such as oxytocin and prolactin are likely contributors (30) . A growing body of evidence suggests that oxytocin is important in regulating energy balance (31) . Furthermore, in a study of female athletes, Lawson et al (32) , noted that oxytocin secretion was positively associated with resting energy expenditure in athletes but not in non-athletes and suggested that oxytocin may have particular importance in energy-deficient states; this could perhaps, for some women, be throughout lactation.…”
Section: Discussionmentioning
confidence: 99%
“…Physiological mechanisms related to lactation that could increase LST need further study, but hormones such as oxytocin and prolactin are likely contributors (30) . A growing body of evidence suggests that oxytocin is important in regulating energy balance (31) . Furthermore, in a study of female athletes, Lawson et al (32) , noted that oxytocin secretion was positively associated with resting energy expenditure in athletes but not in non-athletes and suggested that oxytocin may have particular importance in energy-deficient states; this could perhaps, for some women, be throughout lactation.…”
Section: Discussionmentioning
confidence: 99%
“…Animal studies have demonstrated that PRL is implicated in appetite regulation, body weight, and fat deposition [122]. PRL is involved in the development of pancreatic β-cells and has also been postulated to have functional importance in the adult pancreas [123].…”
Section: Metabolic Riskmentioning
confidence: 99%
“…density lipoprotein cholesterol (LDL-C) [9][10][11][12][13]. It has been suggested that hyperprolactinemia induces hyperphagia leading to obesity [14,15], and that prolactin directly regulates enzymes involved in glucose and lipid metabolism in target organs [16].…”
Section: Hyperprolactinemia and The Association With All-cause Mortalmentioning
confidence: 99%